Descriptive Report on Teachers Skills in Developing Sociable Learning Model at Kindergarten in Bandung - Mohamad Helmi Ismail; Solihin Ichas Hamid; Tuti Istianti (UPI Kampus Cibiru, 2022)
The sociable learning model is a newly built model and is applied in the implementation of community service. Meanwhile, teachers’ experience regarding the model only occurs during training. The inquiry about teacher achievement in implementing the sociable learning model needs to be done to see the teachers’ achievements in developing learning programs by applying the sociable learning models. Such efforts must be made to provide an overview of the training’s success. Descriptive research is conducted using qualitative methods involving several teachers from seven kindergartens located in the city of Bandung. Based on the research findings, the teachers' skills in making the lesson plan are relatively good, as well as their performance in applying sociable learning models in Kindergartens although some of them experience difficulties in designing rule-agreement activities in their lesson plans. By looking at the results of those achievements, it can be concluded that the training has been fairly successful. However, the teachers still need to adapt further to the concept of sociable learning models so that they can design better rule-agreement activities.